Quantitative evaluation of optical coherence tomography angiography images of diabetic retinopathy eyes before and after removal of projection artifacts. Issue 9 (8th June 2018) - Govindaswamy, Nivedhitha; Gadde, Santosh G.; Chidambara, Lavanya; Bhanushali, Devanshi; Anegondi, Neha; Sinha Roy, Abhijit
Abstract : Projection artifacts (PAs) affect the quantification of vascular parameters in the deep layer optical coherence tomography (OCT) angiography image. This study eliminated PA and quantified its effect on imaging. 53 eyes (30 subjects) of normal Indian subjects and 113 eyes (92 patients) of type 2 diabetes mellitus with retinopathy (DR) underwent imaging with a scan area of 3 mm × 3 mm. In this study, a normalized cross‐correlation between superficial and deep layer was used to remove PA in deep layer. Local fractal analysis was done to compute vascular parameters such as foveal avascular zone area (mm 2 ), vessel density (%), spacing between large vessels (%) and spacing between small vessels (%). Before PA removal, vessel density for mild nonproliferative (NPDR), moderate NPDR, severe NPDR and proliferative DR were 42.56 ±1.69%, 40.69 ±0.72%, 37.34 ±0.85% and 35.61 ±1.26%, respectively. After artifact removal, vessel density was 28.9 ±1.22%, 29.9 ±0.56%, 26.19 ±0.59% and 24.02 ±0.94%, respectively. All the vascular parameters were statistically significant ( P  <.001) between normal and disease eyes, irrespective of superficial and deep retinal layers. Parafoveal sectoral analyses showed that temporal zone had the lowest vessel density and may undergo DR‐related changes first. The current approach enabled rapid and accurate quantitative interpretation of DR eyes, without PA. Abstract : Projection artifacts (PAs) hinder the true estimation of vessel density in the optical coherence tomography (OCT) angiography (OCTA) images of the deep retinal plexus. We present an interesting cross‐correlation method to remove PA from the OCTA images of a large set of diabetic retinopathy eyes. Vessel density parameters were significantly altered and this impacted their diagnostic performance. Yellow circles in the figure show the regions after PA removal.